2021
DOI: 10.21037/qims-20-241
|View full text |Cite
|
Sign up to set email alerts
|

CT radiomics features to predict lymph node metastasis in advanced esophageal squamous cell carcinoma and to discriminate between regional and non-regional lymph node metastasis: a case control study

Abstract: Background: Prediction of lymph node status in esophageal squamous cell carcinoma (ESCC) is critical for clinical decision making. In clinical practice, computed tomography (CT) has been frequently used to assist in the preoperative staging of ESCC. Texture analysis can provide more information to reflect potential biological heterogeneity based on CT. A nomogram for the preoperative diagnosis of lymph node metastasis in patients with resectable ESCC has been previously developed. However, to the best of our k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…As for radiomics methods, a clinical-radiomic machine learning model to predict MSI based on computer tomography (CT) in EC and yielded an AUC value of 0.78 in the training set (n=102) and 0.78 in the test set (n=42) (16). The radiomic method has been widely used in other tumors (33)(34)(35)(36)(37), but it faces great challenges in the clinic due to limited interpretability. It is also challenging to delineate the boundaries of EC tumors on CE-CT images.…”
Section: Discussionmentioning
confidence: 99%
“…As for radiomics methods, a clinical-radiomic machine learning model to predict MSI based on computer tomography (CT) in EC and yielded an AUC value of 0.78 in the training set (n=102) and 0.78 in the test set (n=42) (16). The radiomic method has been widely used in other tumors (33)(34)(35)(36)(37), but it faces great challenges in the clinic due to limited interpretability. It is also challenging to delineate the boundaries of EC tumors on CE-CT images.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics analysis of large imaging datasets has been successfully employed in the field of oncology for noninvasively profiling tumor heterogeneity (15,16), and there is a growing interest in devising maps that display the associations between tumor heterogeneity and imaging features (17). This involves the extraction of quantitative features from digital medical images, which enables mineable high-dimensional data to be applied within clinical decision support to offer improved diagnostic, prognostic, and predictive accuracy (18)(19)(20)(21)(22). Radiomics is gaining importance in personalized cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…ESCC prognosis was highly correlated with progression of primary tumor and lymph node metastasis, and thus except primary tumor, lymph node status should also be considered in radiomics model construction. However, many radiomic studies on the progression of ESCC considered only the primary tumor ( 9 - 13 , 28 ). In this study, we evaluated the added value of lymph nodal radiomics in OS prediction and demonstrated that the performance of combined tumor and nodal radiomics was superior to those of either tumor radiomics or nodal radiomics alone.…”
Section: Discussionmentioning
confidence: 99%